The profitability of monetary policy transmission - Alex Hsu; Indrajit Mitra; Linghang Zeng (Federal Reserve Bank of Atlanta, 2023)
We provide firm-level evidence that Federal Open Market Committee announcements have real effects by changing expectations of firm profitability. We use an existing decomposition of a monetary policy shock into a central bank information component (CBI) and a conventional monetary component (MP). We find (1) firms with a higher value of capital asset pricing model (CAPM) beta have a higher investment rate sensitivity to the CBI component; no similar heterogeneity in investment response is observed for the MP component. We also find (2) the heterogeneity in investment sensitivity is due to innovations to firm profitability.
Keywords: E22; E52; G31; 330; monetary policy; Fed information shocks; investments; CAPM beta